Bogomtale: Toward a Sociology of Music Therapy: Musicking as a Cultural Immunogen - Krøier, Julie Kolbe (Tidsskriftet Dansk Musikterapi, 2022)
Bogomtale af Even Ruuds bog fra 2019, Toward a Sociology of Music Therapy: Musicking as a Cultural Immunogen